Do spectators and competitors accept the use of scoring technology in Taekwondo competitions?. (27th July 2011) - Ko, Yong Jae; Cattani, Kevin; Chang, Yonghwan; Hur, Youngjin
The purposes of this study are Davis' (1989) and Davis et al.'s (1992) technology acceptance conception were applied. Multiple regression analyses and descriptive statistics were conducted using data from a survey of a convenience sample of spectators, athletes, and coaches participating in the 2010 US Open Taekwondo Championship. Person-to-person interviews were conducted to expand and enrich the quantitative findings. The results suggested that usefulness and enjoyability were found to be important predictors in developing positive attitude and purchase intention among target samples. The findings of the study are limited by the sample being restricted to a particular product in a very specific context in the USA.